2015
DOI: 10.1186/s12866-015-0493-6
|View full text |Cite
|
Sign up to set email alerts
|

Fratricide activity of MafB protein of N. meningitidis strain B16B6

Abstract: BackgroundNeisseria meningitidis is an inhabitant of the mucosal surfaces of the human nasopharynx. We recently demonstrated that the secreted meningococcal Two-partner secretion protein A (TpsA) is involved in interbacterial competition. The C-terminal end of the large TpsA protein contains a small toxic domain that inhibits the growth of target bacteria. The producing cells are protected from this toxic activity by a small immunity protein that is encoded by the gene immediately downstream of the tpsA gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 21 publications
(42 reference statements)
0
51
0
Order By: Relevance
“…Recent studies have demonstrated that mafB genes encode polymorphic toxins that provide an advantage in competition assays ( 28 , 29 ). In meningococcal strains, mafB genes are present on three Maf genomic islands, termed MGI-1, -2, and -3.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that mafB genes encode polymorphic toxins that provide an advantage in competition assays ( 28 , 29 ). In meningococcal strains, mafB genes are present on three Maf genomic islands, termed MGI-1, -2, and -3.…”
Section: Resultsmentioning
confidence: 99%
“…TpsA induces persister formation upon direct contact with cells lacking sufficient levels of immunity protein [ 179 ]. Very likely, more recently discovered secretion systems that deliver toxins to the target cells [ 180 , 181 ] also contribute to biofilm formation and recalcitrance, a research area that needs to be addressed.…”
Section: Mechanisms Of Biofilm Recalcitrancementioning
confidence: 99%
“…Indeed, downstream of the full-length toxin gene and its cognate immunity gene, there is a variable number of 5′ truncated toxin genes called CT(C-terminal)-cassettes, also associated with their specific immunity gene (Arenas, Schipper, van Ulsen, van der Ende, & Tommassen, 2013;Jamet et al, 2015). These alternative toxic domains could potentially allow antigenic variation by recombination with the full-length toxin gene (i.e., mafB or tpsA; Arenas et al, 2013;Arenas et al, 2015;Jamet et al, 2015). Hence, CT-cassettes constitute a potential reservoir of toxic domains.…”
Section: Polymorphic Toxinsmentioning
confidence: 99%